2014
DOI: 10.1002/jclp.22120
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Problems, Dependency, and Self‐Criticism in Major Depressive Disorder

Abstract: The findings support the interpersonal nature of Blatt's dimensions of depressive experiences. Self-criticism is associated with being too distant or cold toward others as well as greater depression severity, but is not related to the dimension of dominance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
3
32
0
2
Order By: Relevance
“…Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011; Salzer et al, 2011, 2008); our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007; Dinger et al, 2015; Grosse Holtforth et al, 2014; Locke et al, 2016; Quilty et al, 2013; Stangier et al, 2006). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011; Salzer et al, 2011, 2008); our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007; Dinger et al, 2015; Grosse Holtforth et al, 2014; Locke et al, 2016; Quilty et al, 2013; Stangier et al, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…Due to methodological and reporting limitations of many of these studies, conclusions regarding profile descriptors are difficult to draw. In general, these studies suggest that major depressive disorder has a nonassertive and socially avoidant style (Barrett and Barber, 2007; Dinger et al, 2015; Grosse Holtforth et al, 2014; Locke et al, 2016; Quilty et al, 2013; Stangier et al, 2006), social phobia has a nonassertive style (Cain et al, 2010; Kachin et al, 2001; Stangier et al, 2006), and generalized anxiety disorder has an exploitable style (Przeworski et al, 2011; Salzer et al, 2008, 2011). These disorders also seem to have marked elevation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that generalized anxiety disorder, on average, has an exploitable interpersonal style (Przeworski et al, 2011;Salzer et al, 2011Salzer et al, , 2008; our results may differ due to our diagnostic approach. Our results for major depression are consistent with sample averages from previous studies (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006).…”
Section: Psychopathology and Interpersonal Problemssupporting
confidence: 91%
“…Due to methodological and reporting limitations of many of these studies, conclusions regarding profile descriptors are difficult to draw. In general, these studies suggest that major depressive disorder has a nonassertive and socially avoidant style (Barrett and Barber, 2007;Dinger et al, 2015;Grosse Holtforth et al, 2014;Locke et al, 2016;Quilty et al, 2013;Stangier et al, 2006), social phobia has a nonassertive style (Cain et al, 2010;Kachin et al, 2001;Stangier et al, 2006), and generalized anxiety disorder has an exploitable style (Przeworski et al, 2011;Salzer et al, 2008Salzer et al, , 2011. These disorders also seem to have marked elevation.…”
Section: Introductionmentioning
confidence: 94%
“…In past investigations that explored the relation between the DEQ Dependent (Anaclitic) and Self‐Critical (Introjective) scales with the IPC, researchers have found in non‐clinical, inpatient and outpatient populations that the Dependent factor of the DEQ is associated with difficulties related to high Affiliation and low Dominance (Alden & Bieling, ; Desmet, Vanheule, Meganck, Verhaeghe, & Bogaerts, ; Dinger et al , ; Gonzalez & Jenkins, ; Wiseman, Raz, & Sharabany, ) and the Self‐Critical factor is associated with difficulties related to low Affiliation (Alden & Bieling; Desmet et al ; Dinger et al ; Wiseman et al ).…”
mentioning
confidence: 99%